(untitled) (Altre Modernità, 2014)
In this paper, I wish to highlight some of the main characteristics of the autobiographic writing by Glikl Hamel (1645-1724), a German Jewess who wrote her memories. She knows she is doing something that no woman has done before in Yiddish literature. She carefully mingles several literary genres, mixing stories with practical suggestions, proverbs, aphorism, parables, and elements of the so called Muser-literatur, books of moral behavior and instructions on how to be an observant Jew. The author was forty-five years old when she began to write, and her maturity is clearly present in the text, where she presents herself as well aware of what she wants to write, why and how. Glikl often relates about historical events. In particular here two examples are given, one about the relation with some Christian merchants, and the second about the impact of the news on Shabbetay Zevi, the false messiah, on her community.